Investigating the healthcare pathway through patients' experience and profiles: implications for breast cancer healthcare providers - Emna Cherif; Elisabeth Martin-Verdier; Corinne Rochette (BMC, 2020)
Abstract Background Healthcare systems are facing many changes. Particularly, patients are more engaged in the care process. The medical perspective of the process is insufficient to provide patients with high quality care and service personalisation. This research presents an attempt to complete this medical perspective through an experiential perspective, especially for chronic diseases such as cancer. We investigated patients' experiences and profiles to reach a deeper understanding of their needs and expectations when they confront the disease. The objectives of this research were to model the key stages underling the patient pathway and to identify the challenging touch points of the interactions between patients and healthcare providers. Bringing together findings of patient experience, pathway, and profiles would help all the stakeholders involved to develop better practices for the healthcare process. Methods A qualitative observational nethnography on a French specialized forum for breast cancer patients "les Impatientes" was conducted. A total of 967 reviews were collected over a complete year period from all over France. Thematic and lexicometric content analysis were performed according to the experience dimensions, the pathway stages and touch points, as well as the patients' profiles. Results Data analysis shows that the healthcare pathway experienced by the patients is built around three stages. The discovery stage is closely related to the emotional dimension regarding the patient and physician relationship. The examination stage is characterized by a more technical and informational needs for the types of treatments. The follow-up and survivorship stage illustrates the patients' need to assess the treatments' effectiveness and the quality of the follow-up. Moreover, three profiles of patients were identified. The newcomers, the altruists and the autonomous are characterized by different attitudes depending on the stage of the healthcare pathway they were living. Conclusions Our research presents an original modelling of the patient pathway and profiles beyond the medical process. It gives practical tracks to improve the healthcare pathway. Patients expect healthcare providers to integrate and strengthen several challenging touch points in order to create satisfactory patient experiences and high quality service.